2016
DOI: 10.17951/lsmll.2016.40.1.116
|View full text |Cite
|
Sign up to set email alerts
|

Washback effects of a high-stakes exam on lower secondary school English teachers’ practices in the classroom

Abstract: The aim of the article is to investigate the effects of the foreign language section of TEOG (Transition Examination from Primary to Secondary Education) on language teacher practices in the classroom. The participants of the study include 30 English language teachers working at lower secondary schools in Turkey. The results of the study indicate that language teacher practices in the classroom are greatly affected by several factors such as the style and content of the language exam. The main harmful washback… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…However, some teachers did experience confusion in terms of the objectives listed in the textbooks. The negative washback was more severe in the study on the washback of the foreign language section of TEOG in Turkey by Kılıçkaya (2016) who observed that the teachers were given textbooks selected by the Ministry of Education. The adoption of these textbooks was mandatory, so all the teachers had to use them.…”
Section: Negative Washbackmentioning
confidence: 99%
See 4 more Smart Citations
“…However, some teachers did experience confusion in terms of the objectives listed in the textbooks. The negative washback was more severe in the study on the washback of the foreign language section of TEOG in Turkey by Kılıçkaya (2016) who observed that the teachers were given textbooks selected by the Ministry of Education. The adoption of these textbooks was mandatory, so all the teachers had to use them.…”
Section: Negative Washbackmentioning
confidence: 99%
“…Therefore, Barnes (2016) argued that teachers' reliance on skills checklist prevented a more holistic and process-centered way of teaching. Kılıçkaya (2016) studied the foreign language section of TEOG (Transition Examination from Primary to Secondary Education) in Turkey. The author noted that the secondary school language teachers in the study focused on teaching grammar, vocabulary, and reading which were the major elements of the content of the language section of TEOG.…”
Section: Washback On Course Contentmentioning
confidence: 99%
See 3 more Smart Citations